An investigation into what influences action competence-oriented teaching and learning processes in a school environmental club - James, Alison (Rhodes University, Faculty of Education, Department of Education, 2010)
This interpretive case study sought to determine what influenced action competence-oriented teaching and learning processes in a high school environmental club. The goals were to describe a year of activities, within the TALON environmental club at Hudson Park High School in East London, South Africa and to identify how pedagogical, contextual and relational factors influenced action competence processes amongst club members. I explored how action competence theory and praxis have helped in other school education settings with the aim of establishing better environmental practices. The IVAC model of pedagogy (Jensen & Schnack, 1997) was used as a framework to operationalise action competence processes within the TALON Club. This entailed carefully examining investigative, visioning, action and change processes unfolding through the four themes of the club: plants, animal welfare, waste issues and our community outreach programme at Bongulethu High School. Using questionnaires, interviews, observation and a journal as the main methods of data collection I was able to make five analytical statements that related to the influence of pedagogy, the influence of context and the influence of relational dynamics within the TALON Club. The pedagogical processes were affected by the TALON members wanting to avoid any activities that were 'too much like school'. However this served to compromise the action and visioning phases within the club, resulting in superficial and poorly-informed action-taking. The influence of context served to both enable and constrain action competence processes. The club and school structures therefore shaped the form that fledgling actions took as the TALON members participated in the meetings and outings and fulfilling the traditional expectations of the school community. Relational dynamics and a desire for fun took precedence over the action competence processes. Although the Club members were motivated by a sense of moral responsibility they were unable to articulate this concept into the club activities. In addition there were the power gradients between the educators and members to consider as determinants of the extent of participatory, democratic interactions. This complex interplay of factors influenced the action competence processes in the club. Recommendations were made on how best to work with the concepts of participation and democracy towards improving the reflexivity and knowledge base of both the educators and learners. In this way action competence processes will be better supported within the club in future.
Keywords: Environmental education -- South Africa -- East London; Environmental education -- Activity programs -- South Africa -- East London; Environmental literacy -- South Africa -- East London; Environmental literacy -- Study and teaching -- South Africa -- East London; Active learning -- South Africa -- East London; Competency-based education -- South Africa -- East London; Teacher-student relationships -- South Africa -- East London